Evaluation of an Erns-based enzyme-linked immunosorbent assay to distinguish Classical swine fever virus–infected pigs from pigs vaccinated with CP7_E2alf. (July 2015) - Pannhorst, Katrin; Fröhlich, Andreas; Staubach, Christoph; Meyer, Denise; Blome, Sandra; Becher, Paul
Infections with Classical swine fever virus (CSFV) are a major economic threat to pig production. To combat CSF outbreaks and to maintain trade, new marker vaccines were developed that allow differentiation of infected from vaccinated animals (DIVA principle). The chimeric pestivirus CP7_E2alf was shown to be safe and efficacious. Its DIVA strategy is based on the detection of CSFV E rns -specific antibodies that are only developed on infection. However, for the new marker vaccine to be considered a valuable control tool, a validated discriminatory assay is needed. One promising candidate is the already commercially available enzyme-linked immunosorbent assay, PrioCHECK CSFV E rns ELISA (Prionics BV, Lelystad, The Netherlands). Four laboratories of different European Union member states tested 530 serum samples and country-specific field sera from domestic pigs and wild boar. The ELISA displayed a good robustness. However, based on its reproducibility and repeatability, ranges rather than single values for diagnostic sensitivity and specificity were defined. The ELISA displayed a sensitivity of 90–98% with sera from CSFV-infected domestic pigs. A specificity of 89–96% was calculated with sera from domestic pigs vaccinated once with CP7_E2alf. The ELISA detected CSFV infections in vaccinated domestic pigs with a sensitivity of 82–94%. The sensitivity was lower with sera taken ≤21 days post-challenge indicating that the stage of CSFV infection had a considerable influence on testing. Taken together, the PrioCHECK CSFV E rns ELISA can be used for detection of CSFV infections in CP7_E2alf-vaccinated and nonvaccinated domestic pig populations, but should only be applied on a herd basis by testing a defined number of animals.